ANALISIS TERHADAP CETAK BIRU BANK INDONESIA PERIODE 2002-2011 UNTUK PENGEMBANGAN PERBANKAN SYARIAH INDONESIA - Lilik Rahmawati (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2011)
Research entitled â€œAnalysis of the blue print of bank Indonesia for the development of Sharia banking in Indonesia period 2002-2011â€ aims to find out the blueprint of Islamic banking 2002-2011 issued by Central Bank of Indonesia, described the already realized targets of the blueprint of Islamic banking and those which not yet realized, also find out the factor which causes the targets the blueprint of Islamic banking were unrealized. This research is a descriptive research with in-depth analysis method. Data collection methods used was observations and interviews. The results showed that the targets of Indonesian Central Bankâ€™s blue print covering the four things; first, adherence to the principles of Sharia; second, prudence; third, the improvement of operational efficiency and high competitiveness; fourth; stability and expediency of Islamic banking system for the economy. Blueprint objectives outlined in the strategic initiatives that are generally already implemented include: improving the understanding of Islamic finance, facilitating the formulation of norms of Islamic finance, conducting studies in surveillance and integrated arrangement system, refining the provisions of office network, developing â€œexit and entryâ€ policy settings, enhancing the quality of human resources, creating strategic alliances with related agencies, devising the concept of the â€œtakafulâ€ deposit, pushing the involvement if rater institutions in banking activities, and encouraging an increasing in the role of financing with profit-loss sharing method. The objectives outlined in the strategic initiatives that have not been implemented were: the development of the concept of incentives for adherence to the principles of the Sharia, the development of real time supervision, the fulfillment of the needs of people who want Sharia banking services throughout Indonesia with 5% market share, the materializing of the Islamic banking â€œkaffahâ€ functions, and the ability to serve all segments of the community. The factors those cause unimplemented strategic initiatives were the lack of knowledge and understanding of the people about Islamic banking; the lack of human resources with sufficient skill and capability in Islamic economy especially about the laws relating to Islamic banking, the scarcity of funds for socialization and information technology needs, also the assumption of 5% market share defined in accordance with the fact that the current Islamic banks consumers arenâ€™t only muslims but also non-Muslim community